Variasi Molekuler Gen Reseptor Melanokortin-4 pada Monyet Ekor Panjang - Arta Putra, I Gusti Agung; Sajuthi, Dondin; Duryadi Solihin, Dedy; Roro Dyah Perwitasari, Raden (Jurnal Veteriner, 2010)
Melanocortin-4 receptor (MC4R) is one of G protein-coupled receptors that plays an important role inregulation of energy homeostasis. MC4R mutations constitute the most common cause of human obesity.The study was conducted in order to investigate the variation of MC4R gene in Macaca fascicularis and itsassociation with obesity as a model of human obesity. Forty eight adult male macaques from Bali (Ubudand Uluwatu), East Java (Alas Purwo and Baluran), and Sumatera island (Palembang) were used in thisresearch. The animals had been anaesthetized using ketamine (10 mg/kg body weight) and xylazine (2mg/kg body weight) before collecting blood samples and phenotypic data (weight, crown rump length. Bloodsamples were used as source of DNA. To determine MC4R variation, coding region of this gene wasamplified and sequenced. The results showed that 20 variations sites were identified and 13 of them werenon-synonymous. Among the non-synonymous mutations, five mutations were only found in obese macaque;two mutations were found both in obese and non-obese macaque; and six mutations were only found in nonobesemacaque .
Keywords: cynomolgus macaque (Macaca fascicularis), obesity, melanocortin-4 receptor